2013
DOI: 10.1002/er.3081
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable RuO2/SnO2nanocomposites as anode electrocatalysts in a PEM water electrolysis cell

Abstract: SUMMARY This work explores the opportunity to reduce the cost and enhance the stability of RuO2 as an oxygen evolution reaction catalyst by coating RuO2 on chemically stable SnO2 support. Nano‐sized RuO2/SnO2 composites of different mass ratios of RuO2 to SnO2 (0.45:1, 0.67:1, and 1.07:1) were synthesized using solution‐based hydrothermal method. The physicochemical properties of the RuO2/SnO2 were studied by scanning electron microscopy, X‐ray diffraction, transmission electron microscopy, and N2 adsorption–d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 38 publications
0
27
0
2
Order By: Relevance
“…Binary mixtures with Sn have been a controversial topic in the field of OER catalysis. Several studies have investigated Sn mixtures with Ir or Ru and found good to outstanding effects on activity and stability during different operation periods ranging from 250 h at 0.25 A cm −2 to 500 h at 0.5 A cm −2 in a PEM electrolyzer cell (80 °C) ,. However, in a conventional solution‐based hydrogen cell (50 °C, 6 n H 2 SO 4 ), Ir 0.5 Ru 0.5 O 2 outperforms the ternary mixture with 50 wt % tin by several hundred hours (1200 versus 800 h at 1 A cm −2 ) .…”
Section: Degradation Mechanisms and Mitigation Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Binary mixtures with Sn have been a controversial topic in the field of OER catalysis. Several studies have investigated Sn mixtures with Ir or Ru and found good to outstanding effects on activity and stability during different operation periods ranging from 250 h at 0.25 A cm −2 to 500 h at 0.5 A cm −2 in a PEM electrolyzer cell (80 °C) ,. However, in a conventional solution‐based hydrogen cell (50 °C, 6 n H 2 SO 4 ), Ir 0.5 Ru 0.5 O 2 outperforms the ternary mixture with 50 wt % tin by several hundred hours (1200 versus 800 h at 1 A cm −2 ) .…”
Section: Degradation Mechanisms and Mitigation Strategiesmentioning
confidence: 99%
“…Despite these reports, the formation of a single‐phase alloy of Ru/Ir/Sn is highly debated. The reported catalytic results vary from no activity loss to a total loss of activity upon reducing the noble metal content . Figure shows the phase diagram for rutile phase iridium tin oxides calculated by Wang et al .…”
Section: Degradation Mechanisms and Mitigation Strategiesmentioning
confidence: 99%
“…Hydrogen possesses outstanding properties as an energy source, such as carbon neutrality, high efficiency, and nontoxic to environment . Electrocatalysis is an important emerging technology, because it is an inexpensive, clean, and environmentally friendly source of hydrogen energy . It is a simple process by which the strong bonds in water are broken to yield oxygen and hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…RuO 2 À SnO 2 composite oxides have been widely investigated as dimensionally stable anodes in chloro-alkali industry and oxygen evolution catalysts in water electrolysis [1][2][3][4][5][6][7] due to their excellent electrochemical properties. In addition, RuO 2 /SnO 2 also displays high reactivity and stability for HCl oxidation to produce Cl 2 , which is known as Deacon reaction.…”
Section: Introductionmentioning
confidence: 99%